Resilience of Islamic Boarding Schools: Analyzing the Role of Islamic Social Finance in Mitigating Economic Shocks - Anas Alhifni; Biyanti Ahwarumi (Institut Bisnis dan Informatika Kesatuan, 2025)
This study provides a comprehensive analysis of the role of Islamic social finance in enhancing the economic resilience of Islamic boarding schools during the post-pandemic era. Employing a qualitative multiple-case study design, data were meticulously collected through in-depth interviews, participant observations, and extensive documentary analysis from three preeminent Islamic boarding schools. The findings reveal that Islamic social finance instruments encompassing Zakat, Infaq, Sadaqah, and Waqf (ZISWAF), alongside Islamic boarding schools-led business initiatives, were strategically deployed to mitigate the profound economic shocks precipitated by the COVID-19 pandemic. Three primary mechanisms were identified: financial cushioning during acute operational disruptions, entrepreneurial adaptation through innovative business model restructuring, and community empowerment via targeted socio-economic programs. The synergistic integration of Islamic social finance with Islamic boarding schools’ business enterprises was found to be a critical determinant of institutional sustainability, enabling the preservation of educational continuity and the enhancement of community welfare. This study contributes a novel conceptual model of Islamic social finance-mediated resilience, which demonstrates how religiously-grounded financial mechanisms empower traditional institutions to navigate contemporary crises through a strategic fusion of spiritual capital, social networks, and entrepreneurial acumen.